Effect of the addition of ultrafine aluminum powders on the rheological properties and burning rate of energetic condensed systems; Combustion, Explosion and Shock Waves; Vol. 9, № 5 - Popenko E. M.; Gromov A. A. Aleksandr Aleksandrovich; Shamina Yu. Yu.; Ilyin A. P. Aleksandr Petrovich; Sergienko A. V.; Popok N. I. (2007, 2007)
Title screen